Characteristics and Prognostic Analysis of 55 Patients With Pulmonary Sarcomatoid Carcinoma - Sun, Jiachun; Jiang, Zhiyi; Shan, Tanyou; Yang, Ruina; Kong, Dejiu; Rui, Junshuai; Li, Xinyang; Kong, Guoqiang; Chang, Baoping (Frontiers in Oncology, 2022)
Pulmonary sarcomatoid carcinoma (PSC) is a rare and aggressive subtype of non-small-cell lung cancer (NSCLC). Here, we present information on the clinicopathologic characteristics and clinical outcomes of this type of cancer. Clinicopathologic data from 55 patients treated at a single cancer center from January 2011 to December 2019 were retrospectively analyzed. The patients were mostly male (76.4%), with a median age of 66 years and a history of smoking (54.5%). Most had symptoms, and about 60% presented with locally advanced or metastatic disease at diagnosis. Of the 55 cases, 21 were diagnosed by surgical resection. Pleomorphic cancer was the most common subtype (58.1%). With a median follow-up period of 13.2 months, the average survival time of the patients was 16.1 months, and the median survival time was 12 months. The overall survival rates for 1, 2, and 3 years were 52.7%, 18.2%, and 9.1%, respectively. Univariate analysis showed that prognosis of the patients was influenced by tumor size, T stage, metastatic status, and surgery (p < 0.05). Multivariate analysis showed that T stage (p = 0.034) was an independent prognostic factor. There are few reports on the natural history of PSC, and its clinicopathological characteristics remain unclear. Herein, a retrospective review 55 individuals with PSC found that T stage was an independent predictor of survival. Surgical resection was associated with better prognosis.